1996
DOI: 10.1046/j.1464-410x.1996.88213.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prostatectomy on symptom severity and quality of life

Abstract: Prostatectomy is effective in reducing symptoms in most men. Men who experience a substantial reduction in symptoms were more likely to report a favourable outcome. The study confirmed that approximately one-third of men reported an unfavourable result 3 months after their operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
1
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 7 publications
5
71
1
1
Order By: Relevance
“…In a large study by Emberton et al [2] of > 3000 patients treated by TURP the AUA score decreased from a mean of 20.1 at baseline to 7.4 at 3 months. In a randomized study of ILC and TURP by Muschter et al [11], although only published as an abstract to date, the results were excellent in both groups at 12 months (AUA scores of 3.5 and 2.3).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a large study by Emberton et al [2] of > 3000 patients treated by TURP the AUA score decreased from a mean of 20.1 at baseline to 7.4 at 3 months. In a randomized study of ILC and TURP by Muschter et al [11], although only published as an abstract to date, the results were excellent in both groups at 12 months (AUA scores of 3.5 and 2.3).…”
Section: Discussionmentioning
confidence: 94%
“…For many years TURP has been the standard treatment for the patient with symptoms which are too bothersome. TURP is effective but carries a risk of significant complications [2]. Consequently much effort has been devoted to developing new pharmaceutical and interventional treatments that have minimal risks and acceptable effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The overall rate of response of 85.9% was encouraging and the percentage of patients agreeing to some form of assessment (66.8%) compares favourably with similar registers 12 and large audit studies. 13 The ONS tracing service was essential for the follow-up of the remaining patients, informing as to whether they were still alive and the name of each patient's general practitioner via the FHSA. These gave us vital clinical details and the current addresses of the patients, but it is interesting to note that only 23% of those known to be alive, responded to the further contact letter.…”
Section: Discussionmentioning
confidence: 99%
“…2 A report by Schou et al 27 found that, among the 54% of men with clinically significant LUTS (as measured by the DAN-PSS questionnaire) who had reduced ejaculatory volume, the related bother factor was minimal. Indeed, Emberton et al 28 have demonstrated a minimal effect of ejaculatory dysfunction on quality of life even after transurethral resection of the prostate, which carries a much higher risk for retrograde ejaculation than does medical management. In both of these studies, though, the mean age of the population was higher than in the randomized clinical trials for the a-blockers, which may explain the relatively low bother score for ejaculatory dysfunction in these settings.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%